Application Of Stepping Stone And Simplex Methods For Planting Optimization With Topsis As A Determining Criteria - Rudi Hartono; Lukmandono Lukmandono (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
Wonorejo Surabaya Nursery plays an important role in providing plants for green open spaces and urban greening programs. This poses challenges in managing the efficiency of land allocation, plant selection, and seed distribution. This study aims to develop an integrative model using the TOPSIS method to determine the best plant criteria, as well as the Stepping Stone and Simplex methods for optimizing distribution and resource allocation. TOPSIS is used to evaluate plant alternatives based on five main criteria. The results of the study show four priority plants, namely Bromeliad (0.47487), Gandasuli (0.46952), Spiderlili (0.45214), and Adam Hawa (0.59221). The next step is to create a Simplex model with 5 existing constraints, namely land area, water availability, number of workers, personnel working hours, and soil and compost availability. The Z max value is 23.668 with the Adam Hawa decision variable value of 40. For the distribution model, the Northwest Corner method is used and optimized with the Stepping Stone method, resulting in an efficiency of 0.88%. The integration of TOPSIS, Stepping Stone, and Simplex can reduce operational costs and also improve the quality of decision-making to truly support the sustainability of the city's environment.